Optimal Controller Designs for Rotating Machines - Penalising the Rate of Change of Control Forcing - Houlston, Paul Robert; Garvey, Seamus D.; Popov, Atanas A. (2006)
In the context of active control of rotating machines, standard optimal controller methods enable a trade-off to be made between (weighted) mean-square vibrations and (weighted) mean-square currents injected into magnetic bearings. One shortcoming of such controllers is that no concern is devoted to the voltages required. In practice, the voltage available imposes a strict limitation on the maximum possible rate of change of control force (force slew rate). This paper removes the aforementioned existing shortcomings of traditional optimal control.